Long-Term Mootral Application Impacts Methane Production and the Microbial Community in the Rumen Simulation Technique System - Brede, Johanna; Peukert, Manuela; Egert, Björn; Breves, Gerhard; Brede, Melanie (Frontiers in Microbiology, 2021)
Methane emissions by ruminants contribute to global warming and result in a loss of dietary energy for the animals. One possibility of reducing methane emissions is by dietary strategies. In the present trial, we investigated the long-term effects of Mootral, a feed additive consisting of garlic powder (Allium sativum) and bitter orange extracts (Citrus aurantium), on fermentation parameters and the microbial community in the Rumen Simulation Technique (RUSITEC) system. The experiment lasted 38 days and was divided into three phases: an equilibration period of 7 d, a baseline period (BL) of 3 d and experimental period (EP) of 28 d. Twelve fermentation vessels were divided into three groups (n = 4): control (CON), short-term (ST) and long-term (LT) application. From day 11 to day 27, 1.7 g of Mootral was added to the ST vessels; LT vessels received 1.7 g of Mootral daily for the entire EP. With the onset of Mootral application, methane production was significantly reduced in both groups until day 18. Thereafter, the production rate returned to the initial quantity. Furthermore, the short chain fatty acid fermentation profile was significantly altered by Mootral application; the molar proportion of acetate decreased, while the proportions of propionate and butyrate increased. Metabolomic analysis revealed further changes in metabolite concentrations associated with the Mootral supplementation period. The methyl coenzyme-M reductase gene copy number was reduced in the liquid and solid phase, whereas the treatment did not affect the abundance of bacteria. At the end of the BL, Methanomicrobia was the most abundant archaeal class. Mootral supplementation induced an increase in the relative abundance of Methanomassiliicoccales and a reduction in the relative abundance of Methanomicrobia, however, this effect was transient. Abundances of bacterial families were only marginally altered by the treatment. In conclusion, Mootral has the transient ability to reduce methane production significantly due to a selective effect on archaea numbers and archaeal community composition with little effect on the bacterial community.